Survey of Mast Cell Density in Transitional Cell Carcinoma - Hedieh Moradi Tabriz; Maedeh Obohat; Farzan Vahedifard; Arezoo Eftekharjavadi (Iranian Society of Pathology, 2020)
Background & Objective: Transitional cell carcinoma (TCC) is the world's seventh most common tumor and forms more than 90% of urinary bladder tumors. Invasive tumors have had a poor prognosis, even with surgical treatment and chemotherapy. Some studies have found that an increase of mast cells in TCC is related to the tumor grade and its aggressiveness. This study investigated the relationship between mast cell density (MCD) and features of TCC (tumor stage, grade, prognosis, and recurrence).  Materials & Methods: Fifty-one cases with TCC were selected, and MCD was determined by immunohistochemistry (IHC) and Giemsa staining. Mortality rate and tumor recurrence were recorded.  Results: The MCD mean was higher in high-grade tumors than in low-grade tumors (in IHC method: 9.127 vs 5.296; in Giemsa method: 5.512 vs 2.608).  Also, the MCD mean in dead patients was higher than in survived patients (in IHC method: 11.390 vs 6.211; in Giemsa method: 7.460 vs 3.35). Patients with tumor recurrence had a higher MCD mean than those without recurrence (in IHC method: 9.395 vs 5.475; in Giemsa method: 5.715 vs 2.931). Conclusion:  Using mast cell tryptase and Giemsa, MCD has a positive correlation with tumor grade in TCC. Correlations between MCD, recurrence, prognosis, and tumor stage are probably caused by the effect of tumor grade (all with p <0.05).